EKSPERIMENTAL PEMBUATAN TUNGKU BAHAN BAKAR SEKAM GABAH UNTUK MENDAPATKAN TEMPERATUR ALIRAN UDARA PENGERINGANAN GABAH YANG OPTIMAL - Eka Sunitra (Jurnal Teknik Mesin (JTM), 2013)
Subject matter of this research is focused on the manufacture and research tools husk furnace fuels are useful for generating hot air speed that is used to replace electric heating element before. The flow of hot air coming from the furnace will be used to dry husks of grain. Many previous researchers who have made a husk furnace with a variety of methods and construction, replacing the material in order to produce an optimal temperature. In this paper, the authors conducted a study about how to make tools husk furnace and do research on the tool. This research looks at how adaptable tool to generate a stream of hot air. The method I use is the reset method to find the amount of insulation needed to achieve the speed of air drying temperature. Research using laboratory test equipment such as Airflow meter and thermometer. Test data is retrieved (the speed of air temperature and the amount of insulation required). Measurement methods performed directly on the object of research. Test data were analyzed by using the software Microsoft Excel. The data processing results obtained that the most optimum conditions for temperature 42.60 C, the rate of air velocity of 2.84 m/s with number five bulkheadd.